Pregnant Women Satisfaction with the Service of the Health Surveillance Officers for KIA Program - Rinayati Rinayati; Ambar Dwi Erawati; Sri Wahyuning (GLOBAL HEALTH SCIENCE GROUP, 2021)
In the last two years, the maternal mortality rate in Semarang City has increased. In improving the quality of early detection of pregnancy, Semarang City Government has appointed the Health Surveillance Officers of KIA Program/Gasurkes KIA to assist pregnant women. Results of a preliminary survey on pregnant women found problems in the accompaniment process for pregnant women by Gasurkes KIA including lack of arrival frequency, clarity of the meeting time contract, the media used, and the completeness of the materials presented. This study aimed to describe the pregnant women satisfaction with Gasurkes KIA services. This research was conducted using a qualitative approach. The research subjects were seven pregnant women representing seven districts in Semarang City. The data were collected using in-depth interviews and were analyized using content analysis. Gasurkes KIA program seemed neat, confident, had medical records, provided clear health counseling and had good ethics. It is recommended for Gasurkes KIA to increase the use of extension media, make time contracts before mentoring, provide opportunities for questions regarding pregnant women, and increase the confidentiality of pregnant women personal data. Gasurkes Kia has sufficient tangibility, good reliability, good responsiveness, good assurance, and good empathy.